2003
DOI: 10.1176/appi.ps.54.10.1364
|View full text |Cite
|
Sign up to set email alerts
|

Access to and Patterns of Use of Behavioral Health Services Among Children and Adolescents in TennCare

Abstract: Children's access rates for behavioral health services improved even as the TennCare program expanded to cover more children. The system served more youths in part by reducing the volume of services for children receiving treatment and substituting more supportive services. Ongoing performance monitoring for policy making will require enhancements of data monitoring activities by the state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 26 publications
1
22
1
1
Order By: Relevance
“…In fact, studies on Medicaid populations (Callahan, Shepard, Beinecke, Larson, & Cavanaugh, 1995;Dickey, Normand, Norton, Rupp, & Azeni, 2001;Saunders & Heflinger, 2003) have shown increases…”
Section: Abstract Inpatient Psychiatric Hospitalization; Adolescents;mentioning
confidence: 99%
“…In fact, studies on Medicaid populations (Callahan, Shepard, Beinecke, Larson, & Cavanaugh, 1995;Dickey, Normand, Norton, Rupp, & Azeni, 2001;Saunders & Heflinger, 2003) have shown increases…”
Section: Abstract Inpatient Psychiatric Hospitalization; Adolescents;mentioning
confidence: 99%
“…The study concluded that community treatment was not a substitute for inpatient care in the treatment of children with emotional and behavioral problems [103].…”
Section: Tennesseementioning
confidence: 99%
“…5 Despite the rapid infiltration of managed care into the public sector and concerns about quality of care, surprisingly little is known about the effects of Medicaid managed care programs on patterns of mental health care for children. [6][7][8][9] To date, the majority of studies have focused predominantly on adults, yet children, especially those with serious emotional disturbances, may be particularly vulnerable to poorer outcomes within managed care because of their unique characteristics. 8,10,11 Children with emotional and behavioral disorders have complex needs and require a broad array of services from multiple professionals; often, high intensity services over extended periods of time and involvement from multiple systems including public mental health, child welfare, and juvenile justice are necessary.…”
Section: Introductionmentioning
confidence: 99%